2018
DOI: 10.1038/s41598-018-23256-y
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-induced Endothelial Dysfunction is Prevented by Neutrophil Extracellular Trap Inhibition

Abstract: Endothelial dysfunction precedes atherosclerosis and may constitute a critical link between obesity-related inflammation and cardiovascular disease. Neutrophil extracellular traps (NETs) have been shown to promote vascular damage in murine models of autoimmune disease and atherosclerosis. The impact of NETs towards endothelial dysfunction associated with obesity is unknown. Using a diet-induced obesity (DIO) mouse model, this study investigated whether the inhibition or degradation of NETs could reduce the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 37 publications
2
37
0
1
Order By: Relevance
“…The analysis was performed to identify whether NET absorbance is a significant independent predictor of disease progression (overall stage) and adjusting for important available confounders: age, sex, BMI, smoking, diabetes, and comorbidities. All confounders were chosen because they have been shown to induce NET release (39,48,49). Multivariable logistic regression analyses were performed, and model assumptions were tested using graphical representations of residuals, residuals versus main predictor variable graphs, and residuals versus predicted variable graphs.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was performed to identify whether NET absorbance is a significant independent predictor of disease progression (overall stage) and adjusting for important available confounders: age, sex, BMI, smoking, diabetes, and comorbidities. All confounders were chosen because they have been shown to induce NET release (39,48,49). Multivariable logistic regression analyses were performed, and model assumptions were tested using graphical representations of residuals, residuals versus main predictor variable graphs, and residuals versus predicted variable graphs.…”
Section: Methodsmentioning
confidence: 99%
“…In an experimental mouse model of high-fat, high-sucrose diet, the immunostaining for cathelicidin-related antimicrobial peptide (CRAMP), a surrogate marker of NETting neutrophils, was markedly more positive compared to control lean mice and reduced after treatment with Cl-amidine, a PAD4 inhibitor, or DNase [65]. Additionally, the effect of NETs in mediating endothelial dysfunction in obese mice was studied with Cl-amidine administered for 2 weeks or DNase for 8 days, after 8 and 9 weeks of high fat, respectively.…”
Section: Nets In Obesitymentioning
confidence: 99%
“…Additionally, the effect of NETs in mediating endothelial dysfunction in obese mice was studied with Cl-amidine administered for 2 weeks or DNase for 8 days, after 8 and 9 weeks of high fat, respectively. Blocking NETs is beneficial for the recovery from the endothelial dysfunction provoked by the high-fat diet [65]. The main explanation of the role of NETs in obesity-induced endothelial dysfunction might be an abnormal production of MPO.…”
Section: Nets In Obesitymentioning
confidence: 99%
“…Although it is suggested that nicotine-induced upregulation of reactive oxygen species (ROS) production drives cardiac hypertrophy, fibrosis, and inflammation upon chronic exposure (Hu et al, 2011;Ramalingam et al, 2016), limited data is available to describe precise mechanisms underlying nicotine-induced oxidative stress and cardiac dysfunction in vivo. Renin angiotensin system (RAS) is a known regulator of ROS and oxidative stress in other models of cardiovascular diseases such as hypertension, diabetic cardiomyopathy, and heart failure (Huynh et al, 2013;Nagatomo et al, 2014;Wysocki et al, 2014;Wang et al, 2018). Despite evidence for the involvement of oxidative stress in nicotine-induced cardiac pathophysiology, the role of angiotensin II type I (AT1) receptors known to regulate cardiovascular ROS levels in other context, however have not been elucidated in settings of prolonged nicotine administration.…”
Section: Introductionmentioning
confidence: 99%